Perkembangan Pemikiran Akuntansi: Tinjauan dalam Perspektif Sosial Historis - Eva Setia Rini (Ekonomis: Journal of Economics and Business, 2022)
This study tries to describe accounting in a historical social perspective. The review starts from the early history of the emergence of accounting and then the development of accounting thinking. Accounting since its inception until now has increasingly demonstrated its role and function in society as a major system that processes and produces financial information, and will continue to develop in line with changes and developments in society. In a sociological perspective, accounting can be equated with other social institutions because it is considered to make a major contribution to the welfare of society in the long term. Accounting at the concept level, still raises changes and debates among accounting experts and researchers, accounting practices that arise and apply sometimes lead to various interpretations.